Government Bureaucracy Performance in Public Services at the Jangkang Satu Village Office Kubu District Kubu Raya Regency - Ahmad Tohirin; Yulius Yohanes; Ira Patriani (Cita konsultindo, 2024)
Public service is likened to a process, where there are people served, served, and the type of service provided. So that the thought of public services contains basic things that are different from the services provided by the private sector. Especially the Government of Jangkang Satu Village, Kubu District, is required to realize the work discipline of the village apparatus in an effort to improve service effectiveness. Judging from service, it is necessary to improve services with the hope that the services provided will be reliable, accurate, cost-effective, and beneficial to the community. This thesis aims to describe and analyze the Performance of the Village Government Bureaucracy in Public Services at the Jangkang Satu Village Office, Kubu District, Kubu Raya Regency. This research uses descriptive research with qualitative data analysis. The problems that occur are related to the implementation of administrative activities that are not optimal and not effective, the lack of optimal performance of the village government in carrying out its duties to the community, due to the lack of understanding of the apparatus of their main duties and functions, the lack of ability and expertise of the apparatus in the field of information technology, such as the lack of knowledge of the apparatus in operating computers or laptops. The lack of training and skills of the apparatus and the limited facilities and infrastructure supporting the work. In addition, in carrying out its main duties and functions, the apparatus is less responsive and has not fully met the needs of the community. The theory used in describing and analyzing is the theory according to Dwiyanto, namely productivity, service quality, responsiveness, responsibility and accountability. Data collection techniques in this research are observation, interviews and documentation. The informants in this research are the Head of Jangkang Satu Village. Village Secretary, Head of Administration and General Affairs, Head of Service Section, Head of People's Welfare Section and Jangkang Satu Village Community. From the results of this study, it can be seen that the ability and expertise of the apparatus in carrying out their main duties and functions are still low, which has an impact on the performance of the village government. Therefore, it is expected to improve human resources through training and skills, adding facilities and infrastructure to support the work of the apparatus. Keywords: Performance; Government; Public Service.